Analysis of Public Conversation Networks on Prabowo's Program and the Future of Jakarta Through Najwa Shihab Podcast - Syafuddin, Khairul (Mediator: Jurnal Komunikasi, 2025)
Discussions on national politics often attract public participation. This happened in Najwa Shihab's podcast content on YouTube by inviting Ahok. This study aims to identify viewers' conversation patterns on Mata Najwa's uploaded content. Through this analysis, it can be seen that there are expectations from the public that strengthen public opinion that arises from the community. This research approach uses qualitative and quantitative data from the network statistics formed. This research analysis technique uses social network analysis. The results of this study show that the social interaction network formed in this conversation and public opinion is dispersed. The clusters and components of the formed social interaction network tend to be weak. The weak components in this network make the modularity very strong while showing that the public tends to be independent. However, the interaction and arguments of each actor can influence the strength of public opinion.